1001 things your mother told you : and you should have listened to! : quotes, sayings, and timeless wisdom - Pentz, Croft M. (Wheaton, Ill. : Tyndale House Publishers, 2001)
Approved-by-Mother proverbial sayings on over 180 topics covering body, mind and soul. Marriage, parenting, driving, faith, character...Pentz has collected maternal advice on a wide range of topics. After all, "an ounce of mother is worth a pound of clergy". This collection of homespun wisdom offers mother-approved proverbial sayings on over 180 topics, covering body, mind, and soul.
Keywords: Maxims